CONVERSION OF ORGANIZATIONS TO CREATE PROJECT-ORIENTED SYSTEMS - Bilokon, O. I.; Levchynskyi, D. L. (Science and Transport Progress, 2005)
This article reveals the main aspects in the system of organizational structure and integration at transition to a project-oriented organization.